Mengurai Akar Kekerasan: Peran Orang Terdekat Dalam Advokasi Dan Perlindungan Anak - Zakiyyah, Citra Junita; Fadhilah, Ningsih (STAI Al-Amin Gersik Kediri Lombok Barat NTB, 2025)
Child abuse is a complex and profound issue, often involving various internal and external factors. This article examines the role of close individuals, such as family, peers, and the educational environment, in the advocacy and protection of children from violence. The primary focus of this research is how the interactions between children and their close ones can serve as early preventers and protectors against violence. The family, as the first environment encountered by the child, plays a crucial role in creating a sense of security and providing physical and emotional protection. Peers, while they can be a source of support, can also contribute to worsening the situation through bullying and verbal abuse, requiring active intervention by adults. The educational environment is also considered an important factor in educating children about their rights, as well as how to recognize and report violence. This article suggests that educational programs focused on positive parenting, emotional management, and healthy communication within families can raise public awareness about the dangers of child abuse. Additionally, increasing accessibility to legal and psychological services, as well as legal assistance for victims, is crucial to ensure that children can obtain the help they need. The research concludes that a collective effort from families, peers, education, and society as a whole is essential in creating a safe environment for children and protecting them from violence.